Ethnic diversity and informal intra- and inter-ethnic contacts with neighbours in The Netherlands: A comparison of natives and ethnic minorities. (February 2014) - Huijts, Tim; Kraaykamp, Gerbert; Scheepers, Peer
We have examined the extent to which ethnic diversity in neighbourhoods and municipalities in The Netherlands is related to personal contact with neighbours from ethnic in-groups and out-groups among the native majority as well as among ethnic minorities. The results indicate that ethnic diversity is negatively related to personal contacts with native neighbours, but positively to personal contacts with neighbours from other ethnic groups. This applies equally to native respondents and Turks and Moroccans, rejecting Putnam's hunkering-down hypothesis and ethnic competition theory. Instead, ethnic diversity increases meeting opportunities with ethnic minorities while decreasing meeting opportunities with the native majority.